Hepatitis A beyond childhood causing diagnostic and therapeutic challenges in Addis Ababa, Ethiopia - Abate Bane Shewaye; Kaleb Assefa Berhane; Amsalework Daniel Fanta (PLoS ONE, 2025)
Background Hepatitis A is an acute viral infection of the liver caused by hepatitis A virus (HAV) that is acquired through the feco-oral route. It has the highest incidence among the four major acute viral hepatitis types (A, B, C, and E) and usually occurs in early childhood. However, the prevalence of acute hepatitis A has recently increased among teenagers and young adults, and it is usually misdiagnosed. This study emphasizes the significance of awareness among healthcare workers about the increasing incidence of acute hepatitis A among this group to ensure accurate diagnosis and appropriate management. Methods A hospital-based retrospective cross-sectional study was employed. Fifty-eight confirmed acute HAV patients who visited Adera Medical and Surgical Center (AMSC) between August 2023 and January 2024 were enrolled. Sociodemographic, clinical, and laboratory parameters and documented management data, including hospitalization and any trial of antibiotic treatment before considering HAV or in the course of the illness, were collected. The data were entered and analyzed using SPSS (SPSS, Version 26.0). Results The sex ratio was similar, with a slight male predominance (M/F = 1.07). The mean age [± SD] of the patients was 19.3[± 8.8] years. Thirty-nine (67.2%) of the patients were students, and all of the patients were from Addis Ababa. Vomiting (82.8%), anorexia (70.7%) and yellowish discoloration of the eyes (62.1%) were the most common presenting symptoms, while icteric sclera 44 (75.9%) and epigastric tenderness 17 (29.3%) were the most common physical findings. More than half of the patients (55.2%) were initially misdiagnosed with typhoid fever (TF) (46.8%), peptic ulcer disease (PUD) (31.2%) or urinary tract infection (UTI) (15.6%). All patients recovered fully, and liver function tests (LFTs) normalized with supportive care within 2–4 weeks. Conclusion This study revealed the shift in the age of HAV susceptibility and subsequent infection towards adolescents and young adults (mean [± SD] age 19.31 [± 8.8] years) in our cohort, with more than half of the patients (55.2%) initially being misdiagnosed with TF, PUD or UTI, causing diagnostic and treatment challenges. This necessitates heightened awareness among healthcare workers and the public. Early HAV diagnosis through targeted laboratory investigations and avoiding unnecessary antibiotics are crucial for effective management and prevention via hygienic and immunization strategies.